Synthesis, and antimicrobial and anticancer activities of sodium acrylate copolymers - Torgut, Gulben; Pihtili, Guzin; Sonmez, Pinar Erecevit; Erden, Yavuz; Kirbag, Sevda (Sage Publications Ltd, 2020)
This study was designed to synthesize poly(sodium acrylate-co-N-isopropylacrylamide) via aqueous free-radical polymerization using the 2,2 '-azobisisobutyronitrile initiator system at 60 degrees C. The structural characterization of the copolymer was determined by Fourier-transform infrared spectroscopy. The polymer was synthesized in two different ratios, namely, poly(NaAc-co-NIPA1:1) and poly(NaAc-co-NIPA2:1), to investigate whether it affects their antibacterial-antifungal activities and anti-tumour effects. When the antimicrobial activities of different proportions of the copolymer extracts prepared with pure water were examined using the agar disc diffusion sensitivity test (at 120 mu L: 10.8 mg/mu L), it was observed that they had effect at increasing rates against all the bacteria, yeasts and dermatophyte fungi such as Staphylococcus aureus COWAN 1, Staphylococcus cohnii ATCC 29974, Bacillus megaterium DSM 32, Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25922, Klebsiella pneumoniae FMC 5, Pseudomonas aeruginosa DMS 50071 SCOTTA, Candida albicans FMC 17, Candida glabrata ATCC 66032, Trichophyton sp. and Epidermophyton sp. The results of this study revealed that the obtained copolymers have significant effects on the treatment of diseases. In addition, the anti-tumour activities of the poly(NaAc-co-NIPA1:1) copolymer on human breast (MCF-7) and ovarian cancer (A-2780) cell line were specified and it was determined that high doses of the copolymer showed anti-tumour effects on both types of cancer cell lines. Also, this article reviews its antimicrobial and anticancer activities that will be of help for future scientists.
Keywords: Bioactive polymers; synthesis of copolymer; antibacterial properties; antifungal properties; anti-tumour activity